The Investigation of the Awareness of Osteoporosis in Postmenopausal Women - Ahmet Ergin; Güngör Akçay (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2017)
Background and Aims: The awareness of osteoporosis is essential of treatment. We investigated the awareness of osteoporosis in the patients with postmenopausal women in the region of Northeastern Anatolia, Turkey. Methods: Two hundred forty postmenopausal women were included into this study. We detected the age of menopause, the consciousness of osteoporosis, dual x-ray absorptiometry reports, habits of regular walking, drinking of milk, used to calcium and vitamin D supplementation or any antiosteoporotic medicine. Statistical analysis was made by SPSS-20 and data were expressed as mean, standard deviation, minimum- maximum and percent (%). Results: The average age of menopause was 11.7 ± 8.3 years. 90.5% were have the awareness of osteoporosis in the patients with postmenopausal. 71.6% had DXA reports and the percentage of regular consumption of vitamin D and calcium were 60.5%. Unfortunately, the habits of regular walking (5 km or 10.000 steps per day), the regular consumption of milk (1.0 L per day) and used to any drugs for osteoporosis were low, respectively 23.4%, 0.5%, and 9.4%. Conclusions: In our study the awareness of osteoporosis among the postmenopausal women were high. Unfortunately, the percentage of prevention and therapeutic intervention for postmenopausal osteoporosis were low. This condition may improve with the effort of health personals and used to media canals.